Climate and environmental changes of the Lateglacial transition and Holocene in northeastern Siberia: Evidence from diatom oxygen isotopes and assemblage composition at Lake Emanda. (1st May 2021) - Kostrova, Svetlana S.; Biskaborn, Boris K.; Pestryakova, Luidmila A.; Fernandoy, Francisco; Lenz, Marlene M.; Meyer, Hanno
Abstract: A new dataset from Lake Emanda provides insights into climate and environmental dynamics in an extreme continental setting in northeastern Siberia. The δ 18 Odiatom record is supported by diatom assemblage analysis, modern isotope hydrology and atmospheric circulation patterns. The data reveal a relatively cold oligotrophic freshwater lake system persisting for the last ∼13.2 cal ka BP. Most recent δ 18 Odiatom (+21.5‰) combined with present-day average δ 18 Olake (−16.5‰) allows calculating Tlake (∼21 °C), reflecting summer conditions. Nonetheless, the δ 18 Odiatom variability is associated with changes in δ 18 Olake rather than with Tlake . An obvious shift of ∼2‰ in the δ 18 Odiatom record at 11.7–11.5 cal ka BP accompanied by significant changes in diatom assemblages reflects the onset of the Holocene. Relatively high δ 18 Odiatom during the Early Holocene suggests relatively warm and/or dry climate with associated evaporation effects. The absolute maximum in δ 18 Odiatom of +27.7‰ consistent with high values of diatom indices at ∼7.9–7.0 cal ka BP suggests a Mid Holocene Thermal Maximum. A continuous depletion in δ 18 Odiatom since ∼5.0 cal ka BP is interpreted as Middle to Late Holocene cooling reaching the absolute minimum at 0.4 cal ka BP (i.e. the Little Ice Age). An overall cooling trend (∼0.3‰ 1000 yr −1 ) throughout the Holocene follows decreasing solar insolation. The pattern of the Lake Emanda δ 18 Odiatom record is similar to that obtained from Lake El'gygytgyn suggesting a common "eastern" regional signal in both records, despite their hydrological differences. Presently, atmospheric moisture reaches the study region from the west and east with ∼40% each, as well as ∼20% from the north. Graphical abstract: Image 1 Highlights: Climate and environmental dynamics of NE Siberia based on lacustrine diatom assemblages and oxygen isotope composition. Response of a highly continental lake to hydrological changes in the catchment. Emphasizes the sensitivity of the region to hemispheric climate forcing, along with the impact of local factors.